Wuchereria bancrofti 20/22 a homologue of abundant larval transcript L3 stage filarial antigen: molecular and immunological characterization. (October 2014) - Aparnaa, Ramanathan; Mahalakshmi, Natarajan; Harini, Asai; Jeyaprita, Parasurama Jawaharlal; Anugraha, Gandhirajan; Amdare, N. P.; Khatri, V. K.; Reddy, M. V. R.; Kaliraj, P.
Summary The chromadorea abundant larval transcript (ALT) family of proteins contains ALT one of the most studied putative vaccine candidate in experimental filariasis. This study reports the characterization of Wuchereria bancrofti 20/22 (Wb20/22) as a member of chromadorea, the ALT family of proteins from the L3 stage of W. bancrofti. The high reactivity with serum from the endemic normal (EN) population suggests that Wb20/22 could be a target of elicit protective immunity. The glutamic acid‐rich region of Wb20/22 was predicted to harbour the longest linear B‐cell epitope by insilico prediction tools. The significance of this region was revealed by studying the mutant form of Wb20/22, without acidic domain (WOAD) which was cloned, and the immune response was compared with Wb20/22. The signal sequence of Wb20/22 was also an immunodominant region, and mutant construct without signal sequence (WOSS) was cloned and characterized. The peak antibody titre elicited by WOAD was higher than Wb20/22 or WOSS, which pointed to the immunomodulatory role of glutamic acid‐rich region. Wb20/22 elicited very high levels of IL‐10 and diminished levels of IL‐4 and IL‐5 which could be the reason for low antibody titre. The prophylactic efficacy of WOAD conferred protection (62·26%) which was higher than Wb20/22 (49·82%) and WOSS (54·78%).